1998
DOI: 10.1038/sj.onc.1202034
|View full text |Cite
|
Sign up to set email alerts
|

Bax cleavage is mediated by calpain during drug-induced apoptosis

Abstract: The anti-apoptotic molecule Bcl-2 is located in the mitochondrial and endoplasmic reticulum membranes as well as the nuclear envelope. Although its location has not been as rigorously de®ned, the pro-apoptotic molecule Bax appears to be mainly a cytosolic protein which translocates to the mitochondria upon induction of apoptosis. Here we identify a protease activity in mitochondria-enriched membrane fractions from HL-60 cells capable of cleaving Bax which is absent from the cytosolic fraction. Bax protease act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
269
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(290 citation statements)
references
References 49 publications
17
269
2
2
Order By: Relevance
“…It has been shown that Bax can be cleaved either by caspases or calpain. 30,31 However, under the conditions of our experiments, neither the pancaspase inhibitor z-VAD-fmk nor different calpain inhibitors such as E64d, PD150606 and calpeptin were able to prevent cleavage of Bax (Figure 3b). …”
Section: G-csf Inhibits Atra-induced Apoptosismentioning
confidence: 64%
“…It has been shown that Bax can be cleaved either by caspases or calpain. 30,31 However, under the conditions of our experiments, neither the pancaspase inhibitor z-VAD-fmk nor different calpain inhibitors such as E64d, PD150606 and calpeptin were able to prevent cleavage of Bax (Figure 3b). …”
Section: G-csf Inhibits Atra-induced Apoptosismentioning
confidence: 64%
“…43 The amino terminus of BAX has been implicated in BH3 ligand binding, 59 intracellular localization, 89,90 and negative regulation. 91,92 Calpain-mediated cleavage of BAX just prior to its relatively short unstructured loop generates a truncated form with enhanced apoptogenic activity, [93][94][95] which may reflect its functional conversion to a BH3-only-type protein. 96 Multidomain pro-and antiapoptotic proteins contain Cterminal transmembrane domains that insert into the mitochondrial outer membrane.…”
Section: Bcl-2 Family Form and Functionmentioning
confidence: 99%
“…18,19 At the same time, calpains directly proteolyse executioner caspases, mediating their activation, 20,21 as well as proapoptotic Bcl-2 family members that eventually cause the release of apoptogenic factors from the mitochondria involved in the triggering of the caspase cascade. [22][23][24] While the time course of developmental apoptosis in the mouse retina has been extensively described in several studies, 10,[25][26][27] the biochemical death pathways involved are not fully understood. In particular, relatively little is known about the molecular mechanisms of developmental apoptosis in cone photoreceptors, due to the paucity of cone-specific markers at early stages of development.…”
Section: Introductionmentioning
confidence: 99%